2022
DOI: 10.1002/admi.202201050
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrathin Transparent Radiative Cooling Photonic Structure with a High NIR Reflection

Abstract: What's more, to make the DPRC devices economical and manufactured in large scale, polymers and microspheres are applied. [15,[19][20][21][22] General DPRC applications should selectively emit thermal radiation in the atmospheric window and minimize solar absorption, simultaneously. However, for transparent applications (e.g., transparent electrode, [23,24] display device, [25][26][27] and window [28][29][30][31] ), only visible light (0.38-0.78 µm) is allowed for view or illumination. The rest of the solar rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…The design of selective emitters for radiative thermal management systems depends on two photonic wavelength (λ) spectrums: the visible (VIS) to near-infrared (NIR) and the mid-infrared (MIR) 1 , 4 . Passive cooling structures—materials that can passively cool beneath ambient temperatures—are surfaces engineered from materials such as polymers 2 , 3 , 9 , composites 10 12 , and graphene 13 , 14 to maximize thermal emission in the MIR and minimize absorbed solar radiation (λ = 300–2500 nm) by increasing reflected solar radiation. Methods such as nanostructuring 15 , corrugated structures 6 , 16 , core–shell materials 17 , 18 , and periodic gratings 16 , 19 can be used to induce the opposite effect and increase thermal absorption by enhancing a surface’s anti-reflective behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The design of selective emitters for radiative thermal management systems depends on two photonic wavelength (λ) spectrums: the visible (VIS) to near-infrared (NIR) and the mid-infrared (MIR) 1 , 4 . Passive cooling structures—materials that can passively cool beneath ambient temperatures—are surfaces engineered from materials such as polymers 2 , 3 , 9 , composites 10 12 , and graphene 13 , 14 to maximize thermal emission in the MIR and minimize absorbed solar radiation (λ = 300–2500 nm) by increasing reflected solar radiation. Methods such as nanostructuring 15 , corrugated structures 6 , 16 , core–shell materials 17 , 18 , and periodic gratings 16 , 19 can be used to induce the opposite effect and increase thermal absorption by enhancing a surface’s anti-reflective behavior.…”
Section: Introductionmentioning
confidence: 99%
“…(B) Cross-sectional images of the fabricated TRC: (left) scanning electron microscope image of the TRC (41 μm PDMS/1.2 μm PML), (middle) transmission electron microscope image, and (right) energy-dispersive X-ray spectroscopy map of the PML. (C) The transmitted irradiance through the TRC designed with the QA-active learning scheme (experiment and simulation), the reported TRC in ref , UV-fused silica (measured), and TLSC . The yellow shade presents the solar spectral irradiance.…”
mentioning
confidence: 99%
“…21,22 It has been demonstrated that emitters with unity emission efficiency across the whole M/LWIR regime can be more beneficial than AW-selective emitters for radiative cooling. 22−25 In recent years, there have been several material systems proposed for TRCs, such as stacked multilayers of hydrogenated amorphous Si and SiO 2 ; 26 SiO 2 micropillars fabricated on ZnO/Ag/ZnO films; 27 SiO 2 nanoparticles dispersed in polydimethylsiloxane (PDMS) films; 28 and stacked layers of metal oxide, glass, polymer and hydrogel. 29 However, their designs are mainly based on conventional domain-knowledge-driven design strategies, and their performances are far from that of the ideal TRC.…”
mentioning
confidence: 99%
See 2 more Smart Citations